Inflf luence of Customer Relationship Management and Entrepreneurial Leadership on the Performance of Eldercare Services Business - รุ่งสวรรค์โพธิ์, ดวงสมร (Business Administration and Management Journal Review, 2019)
The objectives of this research were to: 1) investigate the level of customer relationship management, entrepreneurial leadership, and performance of elderly care service business; and 2) examine the influence of the customer relationship management, and entrepreneurial leadership on the performance of elderly care services business. This research employed quantitative methods. The research sample consisted of 400 elderly care services entrepreneurs in Bangkok and metropolitan areas. The sample was obtained by systematic sampling. The sample size was determined based on 10 times the manifest variables. The research instrument was a questionnaire. Data were analyzed by mean, standard deviation and structure equation model. The result of this research showed that: 1) the customer relationship management, entrepreneurial leadership and performance were rated at a high level; and 2) customer relationship management and entrepreneurial leadership had a direct influence on the performance of elderly care services business at a .05 level of statistical significance.